Selective Schooling Systems Increase Inequality - Simon Burgess; Matt Dickson; Lindsey Macmillan (Institute for the Study of Labor (IZA), 2014)
We investigate the impact on earnings inequality of a selective education system in which school assignment is based on initial test scores. We use a large, representative household panel survey to compare adult earnings inequality of those growing up under a selective education system with those educated under a comprehensive system. Controlling for a range of background characteristics and the current location, the wage distribution for individuals who grew up in selective schooling areas is quantitatively more unequal, and the difference is statistically significant. The total effect sizes are large: 14% of the raw 90-10 earnings gap and 18% of the conditional 90-10 earnings gap can be explained by differences across schooling systems.
Keywords: I24; J31; 330; selective schooling; inequality; wages; quantile regression